Students’ Perception of Speaking Activities in the “English for Nusantara” Textbook in the 7th Grade Junior High School - Anindita Risma Salsabila (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
Speaking is the most important skill in foreign language or second language learning (Rao, 2019). However, students face various difficulties in speaking English, including lack of vocabulary and pronunciation, difficulty organizing words, lack of confidence, fear of making mistakes, shyness, anxiety, and lack of motivation (Hidayat & Clarita, 2020; Haryanto et al., 2018; Maji et al., 2022). In facing these problems, an ELT textbook is necessary learning medium to help students develop their speaking skills (Cahyani & Perdana, 2019). The “English for Nusantara” textbook is designed to support English language learning that is relevant to the Indonesian context and cultural values, with a structure that integrates the four language skills, including speaking. Given that the textbook has been in use for three years, it is important to analyze the speaking activities presented in the textbook from students’ perception as textbook users. Therefore, this study was conducted to analyzed students’ perceptions of the speaking activities contained in the “English for Nusantara” textbook in the 7th grade Junior High School Previous studies mostly focused on teacher perceptions, content analysis, Pancasila values, moral values, and gender representation. This study aimed to fill the gap by analyzing students’ perceptions of speaking activities in the “English for Nusantara” in the 7th grade junior high school. There are several types of speaking activities that can be applied in language learning, including discussion, role play, simulation, storytelling, interview, presentation, brainstorming, describing pictures, repetition, and monologue (Kayi, 2012; Harmer, 2007; Celce-Murcia et al., 2014). In the “English for Nusantara” textbook, there are five main types of activities: repetition, dialogues/narrative recitation and role play, describing pictures, discussion, and monologue. According to Cunningsworth (1995), a good textbook
Reuploud file repositiry 25mei 2026_Firli_Tata :: Finalisasi Repositori File 11 Juni 2026_Kurnadi
Keywords: Perception; Activites; Textbook